Are the species of the Genus Avicennia L. (Acanthaceae) a “Superhost” plants of gall-inducing Arthropods in mangrove forests? - SANTOS, Rita de Cassia Oliveira dos (2018)
SANTOS, R. C. O.; FERNANDES, M. E. B. Universidade Federal do Pará, Campus Universitário de Bragança (CBRAG), Faculdade de Ciências Biológicas (FBIO)